Pengaruh NCT Dream Sebagai Brand Ambassador Mie Lemonilo dan Daya Tarik Iklan Terhadap Keputusan Pembelian: (Survei pada konsumen Mie Lemonilo Tasikmalaya) - Dhiyaa Durrotunnashah,; Ari Risman,; Depy Muhamad Pauzy, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the effect of NCT dream as a brand ambassador for lemonilo noodles simultaneously on purchase satisfaction. The influence of NCT dream as a brand ambassador for lemonilo noodles and partial appeal to purchasing decisions. The method used in this study is a quantitative method. With a research sample of 100 people as respondents. Sampling uses non-probability precisely using purposive sampling. And the analytical method used is multiple linear regression analysis, the results of the regression equation Y = 12969.790 + -0.194X1 + 1.168X2. Based on the results of the study, it shows that brand ambassadors are in the Good classification, attractiveness is included in the very good classification and purchasing decisions are included in the good classification. The test results show that brand ambassador and attractiveness simultaneously have a significant effect on purchasing decisions. Partially, brand ambassadors do not have a significant effect on purchasing decisions, then attractiveness has a significant effect on purchasing decisions.